Designing for way-finding as practices – A study of elderly people's mobility. Issue 115 (July 2018) - Meurer, Johanna; Stein, Martin; Randall, David; Wulf, Volker
Abstract: Mobility assistance ICTs have become important companions in daily life as digital affordances have become sophisticated. However, understanding and researching everyday way-finding is still challenging, mainly because of the sheer difficulty of collecting empirical data about concrete occasions of use. Hence, we argue that those methodological challenges make it harder to understand the mobility needs of certain user groups. We aim to address this gap while focusing on elderly people, a user group that has increasingly become a focus of HCI studies, and ask the following questions: (1) What are the everyday way-finding practices of that user group? And (2) how can these be supported by mobility assistance ICTs? For answering them, we developed a methodological framework to study daily mobility as way-finding practices and conducted an interview study with 15 'young elderly' people supplemented with a probing technique. The paper concludes with reflections on the potential for and limits to, the study of, and designing for, way-finding as practices.